Newsletter No. 15 - (:unkn) unknown (My University, 2007)
Information about Wave 2 data collection, Wave 1.5 data release and Wave 3 development is included in this issue, as well as news on recent papers, presentations and publications.
15
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology